2018
DOI: 10.1021/acs.orglett.8b03551
|View full text |Cite
|
Sign up to set email alerts
|

Substituted Dihydroisoquinolinones by Iodide-Promoted Cyclocarbonylation of Aromatic α-Amino Acids

Abstract: Imidazolidinone derivatives of a range of aromatic -amino acids, on treatment with phosgene and potassium iodide, undergo a mild Bischler-Napieralski-style cyclocarbonylation reaction that generates a tricyclic lactam by insertion of a C=O group between amino acid nitrogen and the ortho position of the aryl substituent. Regio-and diastereoselective functionalization of the lactam generates a library of substituted dihydroisoquinolinones and their congeners in enantioenriched form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…23 The differences in reactivity under the two sets of reaction conditions suggest that different intermediates are generated. We propose that KI leads to a transient carbamoyl iodide, 16,24 whereas AlCl3 promotes formation of an N-acylium ion, with the carbamoyl iodide being more sensitive to the geometry of imidazolidinone substituents.…”
Section: Scheme 3 Scope Of the Cyclocarbonylationmentioning
confidence: 97%
See 1 more Smart Citation
“…23 The differences in reactivity under the two sets of reaction conditions suggest that different intermediates are generated. We propose that KI leads to a transient carbamoyl iodide, 16,24 whereas AlCl3 promotes formation of an N-acylium ion, with the carbamoyl iodide being more sensitive to the geometry of imidazolidinone substituents.…”
Section: Scheme 3 Scope Of the Cyclocarbonylationmentioning
confidence: 97%
“…We previously reported that an intramolecular KI-promoted Friedel-Crafts cyclization of N-chloroformylimidazolidinones derived from aromatic amino acids such as L-phenylalanine, provides an efficient synthesis of certain substituted 3,4dihydroisoquinolones (Scheme 1). 16…”
Section: Figure 1 Natural Products Containing the Dihydroisoquinolonmentioning
confidence: 99%
“…N ′‐Alkenylureas 3 may be made by isomerization of their N ′‐allyl congeners, so we began by preparing N ′‐allylureido imidazolidinones 2 (Scheme ) from l ‐alanine. Either the syn or the anti diastereoisomer of 2 a could be made selectively from a common imine intermediate 1 a by choice of conditions, with acylation of the imine with a carbamoyl chloride at elevated temperatures giving syn ‐ 2 a , and anti ‐ 2 a being obtained by acylating N ‐methylallylamine with the anti carbamoyl chloride generated using phosgene and pyridine …”
Section: Methodsmentioning
confidence: 99%
“…The cyclized product (3S,10aS)-3-(tert-butyl)-2-methyl-2,3,10,10a-tetrahydroimidazo [1,5-b]isoquinoline-1,5-dione can be used to get the functionalized dihydroisoquinolinones via the by regio-and diastereose- lective alkylation followed by the acidic hydrolysis of the imidazolidinones to get enantiopure dihydroisoquinolinones carboxylic acids (Scheme 74). [91] S. Cui et al demonstrated the silver catalyzed cascade phosphorylation/cyclization of propene having N-cyanamide to dihydroisoquinolinones. The propene containing N-acylcyanamides on treatment with diphenylphosphineoxide in presence of the 1 equivalent of silver nitrate cyclized to phosphorous incorporated dihydroisoquinolinones.…”
Section: Scheme 42 Synthesis 4-hydroxyalkyl-substituted 34-dihydroimentioning
confidence: 99%